LEGAL AND FINANCIAL STIMULATION OF FOREIGN INVESTMENTS IN SERBIA - Stankovic, Bratislav; Vignjevic Djordjevic, Nada (Journal of Applied Engineering Science, 2017)
In recent decades there have been significant changes in the legal treatment of foreign direct investments. In Serbia, like in other transitional countries, there has been liberalization of rules on foreign direct investments. Parallel to this process, the government began to approve a number of financial and fiscal incentives for foreign direct investments. In principle, it can be concluded that this approach is justified. However, some weaknesses can be observed. In terms of financial incentives, it is noticeable the existence of certain discretionary powers which could be considered excessive. Regarding tax incentives, in our opinion, the possibility of introducing incentives for export activities should be seriously considered. On the other hand, we believe that it is not justified to prescribe different customs treatment for imports of equipment brought to the capital of a company depending on whether such equipment is imported by a domestic or foreign investor. Finally, we are of opinion that it is necessary to undertake a serious study about the effects of investment incentives in order to give a proper assessment of their effectiveness and efficiency.
Keywords: Foreign direct investments; direct investments; financial and fiscal stimulations; directive; foreigners; incentives; investments